Intermediate-Dose versus Standard-Dose Prophylactic Anticoagulation in Patients with COVID-19 Admitted to the Intensive Care Unit: 90-Day Results from the INSPIRATION Randomized Trial - Bikdeli, Behnood; Talasaz, Azita H.; Rashidi, Farid; Bakhshandeh, Hooman; Rafiee, Farnaz; Rezaeifar, Parisa; Baghizadeh, Elahe; Matin, Samira; Jamalkhani, Sepehr; Tahamtan, Ouria; Sharif-Kashani, Babak; Beigmohammadi, Mohammad Taghi; Farrokhpour, Mohsen; Sezavar, Seyed Hashem; Payandemehr, Pooya; Dabbagh, Ali; Moghadam, Keivan Gohari; Khalili, Hossein; Yadollahzadeh, Mahdi; Riahi, Taghi; Abedini, Atefeh; Lookzadeh, Somayeh; Rahmani, Hamid; Zoghi, Elnaz; Mohammadi, Keyhan; Sadeghipour, Pardis; Abri, Homa; Tabrizi, Sanaz; Mousavian, Seyed Masoud; Shahmirzaei, Shaghayegh; Amin, Ahmad; Mohebbi, Bahram; Parhizgar, Seyed Ehsan; Aliannejad, Rasoul; Eslami, Vahid; Kashefizadeh, Alireza; Dobesh, Paul P.; Kakavand, Hessam; Hosseini, Seyed Hossein; Shafaghi, Shadi; Ghazi, Samrand Fattah; Najafi, Atabak; Jimenez, David; Gupta, Aakriti; Madhavan, Mahesh V.; Sethi, Sanjum S.; Parikh, Sahil A.; Monreal, Manuel; Hadavand, Naser; Hajighasemi, Alireza; Maleki, Majid; Sadeghian, Saeed; Piazza, Gregory; Kirtane, Ajay J.; Van Tassell, Benjamin W.; Stone, Gregg W.; Lip, Gregory Y. H.; Krumholz, Harlan M.; Goldhaber, Samuel Z.; Sadeghipour, Parham (Thrombosis and Haemostasis, 2021)
Background Thrombotic complications are considered among the main extrapulmonary manifestations of coronavirus disease 2019 (COVID-19). The optimal type and duration of prophylactic antithrombotic therapy in these patients remain unknown.Methods This article reports the final (90-day) results of the Intermediate versus Standard-dose Prophylactic anticoagulation In cRitically-ill pATIents with COVID-19: An opeN label randomized controlled trial (INSPIRATION) study. Patients with COVID-19 admitted to intensive care were randomized to intermediate-dose versus standard-dose prophylactic anticoagulation for 30 days, irrespective of hospital discharge status. The primary efficacy outcome was a composite of adjudicated venous or arterial thrombosis, treatment with extracorporeal membrane oxygenation (ECMO), or all-cause death. The main safety outcome was major bleeding.Results Of 600 randomized patients, 562 entered the modified intention-to-treat analysis (median age [Q1, Q3]: 62 [50, 71] years; 237 [42.2%] women), of whom 336 (59.8%) survived to hospital discharge. The primary outcome occurred in 132 (47.8%) of patients assigned to intermediate dose and 130 (45.4%) patients assigned to standard-dose prophylactic anticoagulation (hazard ratio [HR]: 1.21, 95% confidence interval [CI]: 0.95–1.55, p = 0.11). Findings were similar for other efficacy outcomes, and in the landmark analysis from days 31 to 90 (HR: 1.59, 95% CI: 0.45–5.06). There were 7 (2.5%) major bleeding events in the intermediate-dose group (including 3 fatal events) and 4 (1.4%) major bleeding events in the standard-dose group (none fatal) (HR: 1.82, 95% CI: 0.53–6.24).Conclusion Intermediate-dose compared with standard-dose prophylactic anticoagulation did not reduce a composite of death, treatment with ECMO, or venous or arterial thrombosis at 90-day follow-up.
Keywords: anticoagulation; heparin; enoxaparin; COVID-19; trial